Self-motivation, teacher effectiveness and academic performance of high achieving students in selected secondary schools in Ibadan, Nigeria (2019)
The study investigated the relationship between self-motivation, teacher effectiveness and academic performance of high achieving secondary school students in Ibadan North Local Government Area of Oyo State. The study adopted the descriptive survey research design of correlational type. Simple random sampling technique was used to select four schools from Ibadan North Local Government Area and in each of the four schools, Slosson Intelligence Test was used to screen the intelligent ones among the Senior Secondary School II students. The school continuous assessment records were carefully looked into in order to randomly select fifty (50) high achieving students in each of the four schools. The participants were two hundred (200) in all. The three main instruments used were Self-Motivation Assessment Scale, Teacher Effectiveness Assessment Scale and Slosson Intelligence Test. Three hypotheses were tested at 0.05 level of significance. Data were analysed using Pearson Product Moment Correlation (PPMC). The result revealed that there was a positive relationship between teacher effectiveness and academic performance of high achieving students (r=0.355): there was positive relationship between self-motivation and academic performance of high achieving students (r=0.4I5); self-motivation and teacher effectiveness had joint significant relationship with academic performance of high achieving secondary school students (r=.2I4). Based on the above findings it was recommended that professional guidance counselors counsel students on the act of self-motivation since it has been discovered that the higher the self-motivation of students, the higher their academic performance. It was also recommended that teachers handling high achieving students should be exposed to capacity building programmes to improve their effectiveness.